Positive, negative, and ambivalent: Indian parents’ attitudes to and mediation methods of children’s digital media use - Sowparnika Pavan Kumar Attavar; Padma Rani (Cogent Social Sciences)
Children’s digital media use in India, particularly in urban family settings, has sharply increased over the years. As children continue to use digital media unprecedentedly, it is essential to know how the environments within which children grow influence children’s digital media activities. In this ethnographic study, we explore whether parental opinions about digital media influence children’s access to and use of digital media and whether parental opinions determine their choice of mediation methods. The results from this study show that parents with positive opinions regarding digital media were liberal in their mediation methods, and those with negative opinions adopted restrictive mediation methods. The study also identified a third approach, which we call ambivalent mediation. Parents adopting this method had mixed opinions about digital media. They were unsure how they should mediate children’s digital media use. Their parental mediation methods were found to be constantly shifting between restrictive and permissive mediation and they failed to implement any one method correctly or consistently. These insights inform that Indian parents need adequate support to become equipped and prepared to manage their children’s digital media practices. This calls for more effective parental guidance programs and policies to promote healthy digital media habits in families.